Corrigendum: Ligand‐Controlled Regio‐divergent Pathways of Rhodium(III)‐Catalyzed Dihydroisoquinolone Synthesis – Experimental and Computational Studies of Different Cyclopentadienyls. Issue 34 (2nd June 2020) - Wodrich, Matthew D.; Ye, Baihua; Gonthier, Jérôme F.; Corminboeuf, Clémence; Cramer, Nicolai
Abstract :